2019
DOI: 10.6007/ijarped/v8-i4/6450
|View full text |Cite
|
Sign up to set email alerts
|

Board Structure and Corporate’s Performance: Evidence from Private Education Companies

Abstract: This paper investigates the effect of board structure of Malaysian private educational companies towards their firm's corporate performance. The average board size in this study is three and the percentage of women on board is about 40%. In addition, seventy six percent of the firm is having women as their director. By examining the relationship between board structure (board size and, woman on board) and the firm performance, our study shows that board size has a significant negative relationship with firm pe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

1
1
0

Year Published

2021
2021
2021
2021

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 32 publications
1
1
0
Order By: Relevance
“…Similarly, board size revealed a positive but not significant influence on ROE of listed commercial banks in CSE. The findings supportSenthuran & Velnampy, (2015) & Razali et al, (2019…”
supporting
confidence: 83%
See 1 more Smart Citation
“…Similarly, board size revealed a positive but not significant influence on ROE of listed commercial banks in CSE. The findings supportSenthuran & Velnampy, (2015) & Razali et al, (2019…”
supporting
confidence: 83%
“…H1a: There is a relationship between board size and ROA H1b: There is a relationship between board size and ROE Razali et al, (2019) & Dissanayake and Dissanayake, (2019) found that women on board show a significant positive impact on firm performance. More women on board may have better corporate performance, as claimed by women are good in terms of understanding the market needs and bringing creativity and quality solutions in decision-making.…”
Section: Board Size and Firm Performancementioning
confidence: 99%